2014
DOI: 10.5194/acp-14-10061-2014
|View full text |Cite
|
Sign up to set email alerts
|

Size distribution, mixing state and source apportionment of black carbon aerosol in London during wintertime

Abstract: Abstract. Black carbon aerosols (BC) at a London urban site were characterised in both winter-and summertime 2012 during the Clean Air for London (ClearfLo) project. Positive matrix factorisation (PMF) factors of organic aerosol mass spectra measured by a high-resolution aerosol mass spectrometer (HR-AMS) showed traffic-dominant sources in summer but in winter the influence of additional non-traffic sources became more important, mainly from solid fuel sources (SF). Measurements using a single particle soot ph… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

18
222
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 192 publications
(240 citation statements)
references
References 70 publications
18
222
0
Order By: Relevance
“…25 The substantial presence of thinly-coated (fresh) rBC suggested by the SP2 data (Figure 4) is consistent with our independently measured V-TDMA observations of externally-mixed characteristics for LV mode particles (Figure 3, Figure S9). These observations are also in agreement with several recent studies that examined the mixing state of rBC from traffic emissions using a range of techniques (China et al, 2014;Kuwata et al, 2009;Liu et al, 2014;McMeeking et al, 2011b;Willis et al, 2016). Willis et al (2016) reported approximately 90% of rBC mass resides in rBC-rich particles using Soot 30…”
Section: Mixing State Of Near-highway Particlessupporting
confidence: 81%
See 2 more Smart Citations
“…25 The substantial presence of thinly-coated (fresh) rBC suggested by the SP2 data (Figure 4) is consistent with our independently measured V-TDMA observations of externally-mixed characteristics for LV mode particles (Figure 3, Figure S9). These observations are also in agreement with several recent studies that examined the mixing state of rBC from traffic emissions using a range of techniques (China et al, 2014;Kuwata et al, 2009;Liu et al, 2014;McMeeking et al, 2011b;Willis et al, 2016). Willis et al (2016) reported approximately 90% of rBC mass resides in rBC-rich particles using Soot 30…”
Section: Mixing State Of Near-highway Particlessupporting
confidence: 81%
“…CC BY 4.0 License. reported to be uncoated or very thinly coated by Laborde et al (2013) and Liu et al (2014) using SP2 measurements in urban environments. Figure 5 compares similar V-TDMA measurements of 100 nm particles at different distances from the highway to examine the evolution of mixing state of particles with downwind transport.…”
Section: Mixing State Of Near-highway Particlesmentioning
confidence: 99%
See 1 more Smart Citation
“…The LEO methodology is detailed in Liu et al 22 : briefly, the scattering signals for the last 200 non-BC scattering-only particles are used to determine the laser profile; the number of data points used for LEO is optimised to represent the scattering signal before the onset of particle volatilisation, and is automatically obtained by comparing the measured signal and laser profile, with uncertainty <12% (from the parametrization of the LEO fitting). Only single particles with successful LEO fitting are included in the calculation of optical properties.…”
Section: Figure Captionsmentioning
confidence: 99%
“…Although a number of laboratory and field studies have investigated the volatility (Kuwayama et al, 2015;May et al, 2013a, b;Li et al, 2016;Biswas et al, 2007;Grieshop et al, 2009) and mixing state (Tiitta et al, 2010;Liu et al, 2014;China et al, 2014;Willis et al, 2016) of traffic-emitted particles using various techniques, they have largely focused on source characterization or measurements at a fixed ambient location. To the best of our knowledge, no studies have been conducted to systematically explore the evolution of volatility and mixing state of near-road aerosols at different distances from the roadway under diverse environmental conditions.…”
Section: Introductionmentioning
confidence: 99%